2014
DOI: 10.1007/s10880-014-9392-5
|View full text |Cite
|
Sign up to set email alerts
|

Child Perceptions of Parental Care and Overprotection in Children with Cancer and Healthy Children

Abstract: Objective The primary aims of this study were to: a) examine child perceptions of overprotection; and b) explore how these perceptions relate to child health and adjustment. Method Children with a prior diagnosis of cancer (n = 205) and children without a history of serious illness (n = 76) reported on parental overprotective and caring behaviors. Children with cancer were recruited from one of four strata based on the elapsed time since their cancer diagnosis (1–6 months; 6–24 months; 2–5 years; > 5 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
2
22
0
9
Order By: Relevance
“…Indeed, a recent study found that children with cancer do not perceive their parents approach to care or protection differently than children without a history of cancer providing early evidence that the proxy problem may be inflated as a function of the method of analysis. [30] The repeated-measure ANOVA examining the discrepancy between child and parent emotional functioning was not significant and there was no significant difference between sibling reports of emotional functioning compared to published norms. [31] Yet, sibling reports of emotional functioning were relatively low compared to other subscale scores and poor agreement between parent and sibling emotional functioning was found.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, a recent study found that children with cancer do not perceive their parents approach to care or protection differently than children without a history of cancer providing early evidence that the proxy problem may be inflated as a function of the method of analysis. [30] The repeated-measure ANOVA examining the discrepancy between child and parent emotional functioning was not significant and there was no significant difference between sibling reports of emotional functioning compared to published norms. [31] Yet, sibling reports of emotional functioning were relatively low compared to other subscale scores and poor agreement between parent and sibling emotional functioning was found.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, taking into account both discrepancy and agreement provides a more complete picture. Indeed, a recent study found that children with cancer do not perceive their parents approach to care or protection differently than children without a history of cancer providing early evidence that the proxy problem may be inflated as a function of the method of analysis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1921] This may be related to cognitive distortion caused by children's immature cognition of disease, over protection by parents and public prejudice against cancer. [22] Although the control group received only routine psychological care, the doctors, nurses, and parents could not provide effective psychological intervention to correct their cognitive distortion and make pediatric cancer patients optimistically adjust to the chemotherapy. Because the qualifications, educational background of the doctors, nurses, and parents were not uniform and lacked inadequate professional psychology knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…La relación con el niño con cáncer, en varias ocasiones, tiene matices de sobreprotección que pueden llevar a un vínculo patológico en el que no solo se ve afectado el sano desarrollo de la personalidad del niño, sino también los sentimientos y metas del cuidador en su rol parental (Hullmann et al, 2010;Tillery et al, 2014). La relación con el resto de la familia se ve afectada por el aislamiento del cuidador, que dedica gran parte de su tiempo, atención, motivación y energía al cuidado del niño enfermo, dejando de lado la relación con su cónyuge u otros hijos (Rech et al, 2013;Williams et al, 2014;Zegaczewski et al, 2016).…”
Section: Insuficiencia Del Rol De Cuidador Del Niño Con Cáncerunclassified